Implementasi Teori operant conditioning dalam Pembelajaran Tahfidzul Quran di PPTQ Muhammadiyah Ibnu Juraimi Yogyakarta - Asyari, Ary (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2020)
This study aims to determine how the implementation of operant conditioning theory in learning tahfidzul quran at PPTQ Muhammadiyah Ibnu Juraimi Yogyakarta. The research method used is descriptive qualitative research. is in PPTQ Muhammadiyah Ibnu Juraimi because the researcher is indeed a wadir of beauty at the PPTQ Muhammadiyah Ibnu Juraimi, the second is in-depth interviews with Muhafidz, the third documentation is by recording every activity, material and other things that are related to research. The data analysis technique is done by reducing the data, presenting the data and drawing conclusions. The conclusions obtained can be tested for correctness by means of data triangulation and informant reviews. The results of the operant conditioning theory research on the importance of reinforcement of a response arising from the stimulus can help improve the performance of students in memorizing the Qur'an.